Virtual Arena for Traditional Arts: Development of a Digital Platform for Cultural Preservation - Hadawiyah Endah Utami; Raden Ary Bhagawan Wijaya (Jurnal Penelitian Pendidikan IPA, 2026)
This article examines the development of Virtual Arena for Traditional Arts, a digital platform designed for the preservation of traditional arts through a technological approach and motion mechanics as elements of digital communication. This research stems from the urgent need to provide an alternative performance space amid the decline of physical stages and the decrease in direct interaction between artists and audiences. The concept of motion mechanics is applied to capture, visualize, and transmit body movements with precision through motion capture technology, so that the aesthetic characteristics of traditional arts remain authentic in virtual format. The digital stage functions as an interactive communication medium that allows the audience not only to observe but also to experience the performance through 3D visualization, dynamic avatars, and virtual reality-based stage design. The research methods included literature studies and system design. The results showed that the integration of motion mechanics with digital stages improved the quality of art representation, expanded the global audience reach, and strengthened real-time user engagement. These findings confirm that virtual arenas have the potential to become a new model of cultural communication in the digital age and an innovative strategy for preserving traditional arts.